2007
DOI: 10.1111/j.1468-2982.2006.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Recurrent Abdominal Pain: A Controlled Study by the Means Of The Child Behaviour Checklist (CBCL)

Abstract: Headache and recurrent abdominal pain (RAP) are common disorders in children and adolescents, frequently referred to paediatricians. Both disorders show similarities in trigger and comorbid factors, their burden on family and individual life, and a paroxysmal trend with risks of chronicization over time. However, very few studies have compared directly headache and RAP. The main aim of this study was to compare the psychological profile of headache and RAP patients vs. healthy controls. A total of 210 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 60 publications
4
51
0
5
Order By: Relevance
“…Even though most children with frequent AP are lacking explanatory organic diseases [1] and a substantial proportion of children exhibits psychological problems [14,17,52], it cannot be concluded that frequent nonorganic AP is caused by psychological factors [11]. FGIDs are thought to be strongly linked to a disordered brain-gut interaction [13]: Stress and unpleasant emotional states lead to hypervigilance and hence to an increase of arousal of the autonomous nervous system and the endocrine system, which may contribute to a heightened sensitivity of the gut and modified gut motility [13,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though most children with frequent AP are lacking explanatory organic diseases [1] and a substantial proportion of children exhibits psychological problems [14,17,52], it cannot be concluded that frequent nonorganic AP is caused by psychological factors [11]. FGIDs are thought to be strongly linked to a disordered brain-gut interaction [13]: Stress and unpleasant emotional states lead to hypervigilance and hence to an increase of arousal of the autonomous nervous system and the endocrine system, which may contribute to a heightened sensitivity of the gut and modified gut motility [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…A part of children with AP is at risk of symptom persistence till adulthood [5,21,24,53]. Children with AP are found to score higher in questionnaires assessing psychopathological symptoms especially internalizing disturbances such as anxiety and other somatic complaints [14,17,52]. They also feature a high rate of psychiatric disorders such as anxiety disorders and depression [4,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, somatization has been associated with psychopathology, particularly anxiety and depression [3,11,16,20,29,33]. Most authors find that the association with internalizing disorders is higher than with externalizing disorders [6,9,10,12,24,28,29].…”
Section: Introductionmentioning
confidence: 97%
“…Many investigations have focused on specific symptoms such as recurrent stomachache or headache [11,16,20,33,41]. Furthermore, most researches have been devoted to studying schoolchildren and adolescents.…”
Section: Introductionmentioning
confidence: 99%